Concept of Positive Aspects of Caregiving: Adapted in Caregivers of Older Person with Dementia - แผนคง อรวรรณ; โปธิบาล ลินจง (Nursing Journal CMU, 2018)
Dementia caregiving is particularly difficult for caregivers. Positive aspects of caregiving are needed to face the uncertainty of care issues in daily life. From the literature review, concepts of positive aspects of caregiving have developed to help explain and lead to find out ways to encouraging positive views in caregiving events. A Kramer’s two-factor adaptation model demonstrates the key sources that influence the caregiver’s appraisal and lead to positive outcomes. The revised stress and coping model identified strategies that can promote a positive emotion of care that consisting of four strategies. These concepts are not completely applied to the Thai context. Therefore, it should be applied among caregivers of older persons with dementia in Thailand.